Prevalencia de brucelosis canina en el Centro de Esterilización Canina y Felina del cantón Pujilí - Ecuador. - Páez Calvopiña, Kléber Paúl (2021)
The purpose of this research was to determine the prevalence of canine brucellosis in the Center for Canine and Feline Sterilization of the Pujilí canton - Ecuador, by detecting antibodies and antigens of Brucella canis in the animals that are cared for in the center belonging to the Decentralized Autonomous Government. Municipal Intercultural of the Pujilí canton, Cotopaxi province, for which 316 male and female canines of reproductive age were sampled, in the period from October 2019 to December 2020. Blood samples were taken in males and females, 216 were processed in situ under the LFIA lateral flow immunochromatography technique for Brucella canis with the commercial use test, Bionote, Inc. Anigen Rapid C. Brucella AbTest Kit® that was performed on samples whole blood and 100 blood serum samples were processed under the indirect IFI immunofluorescence technique in a certified laboratory; the variables taken into account were sex, race, age and reproductive history, using descriptive statistics. For the LFIA lateral flow immunochromatography test, the results obtained were the following: in the variable “sex”, of the 178 sampled females 10.67% were positive, of the 38 sampled males 13.15% were positive; In the variable "race", 165 samples were from crossbred animals of which 10.30% were positive, 51 samples were from animals of other races of which 13.75% were positive; In the variable “age”, 102 samples were from canines of 1-2 years, 11.76% were positive, 93 samples were from canines of 2-5 years, 10.75% were positive, 21 samples were from canines older than 5 years, 9.52 % was positive; for the variable "reproductive history", 201 animals were considered normal, of which 8.45% were positive, 15 animals were considered abnormal, 46.66% were positive. For the indirect IFI immunofluorescence test, the results obtained were the following: in the variable “sex”, of the 81 sampled females, 14.81% were positive, of the 19 sampled males, 10.52% were positive; In the variable "race", 71 samples were from crossbred animals of which 15.49% were positive, 29 samples were from animals of other races of which 10.34% were positive; In the variable “age”, 51 samples were from canines of 1-2 years, 9.80% were positive, 40 samples were from canines of 2-5 years, 17.50% were positive, 9 samples were from canines older than 5 years, on 22.22 % was positive; for the variable "reproductive history", 94 animals were considered normal, of which 14.89% were positive, 6 animals were considered abnormal in and there were no positive cases.